Effectiveness of Using Wind Power Plants (PLTB) in Coastal Areas to Support Energy Needs in National Defense - Gatya, Dyota Arkka; Setyanjana, Andre; Laksmono W, Rudy (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
As the most widely used energy resource, fossil energy is non-renewable energy. At the end of the 20th century, the demand to replace fossil energy with alternative energy became greater with public awareness of renewable energy for the sustainability of nature. One of the renewable energies that is developing rapidly in the world today is the use of wind. Wind energy is a renewable energy that is very flexible, environmentally friendly, and has good work efficiency. In general, Indonesia is still very dependent on electricity supplies from the State Electricity Company (PLN), but several areas, especially the coast and outer islands of the country, have not been touched by PLN. So there is a real need for alternative energy sources that support energy needs for national defense, one of which is through wind energy which is very abundant, especially along the coastline. The aim of writing this work is to optimize the utilization of the potential of wind energy as an alternative electrical power in coastal areas and beaches in Indonesia which can be used for energy needs in guarding the coast on the outer islands. The method used in this research is a systematic literature review method. The results of the literature study show that most of Indonesia's coastal areas have wind speeds between 5 m/s and 10 m/s, which meets the minimum wind speed requirements for wind power plants of 3.3 m/s for small scale. So that in its implementation, the PLTB design can adapt to electrical power needs. For better effectiveness, the use of PLTB can be combined with other sources of electrical energy, for example solar power.